What Do Indigenous Communities Think of the CSR Practices of Mining Companies? - Kepore , Kevin; Higgins , Colin; Goddard , Robert (Journal of Law and Governance, 2013)
This paper examines how one indigenous community in the Western Province of Papua New Guinea (PNG) views the social responsibility initiatives of OK Tedi Mining Ltd (OTML). This mining operation has been controversial since its inception, and various operators of the mine have sought to engage the community and to undertake a number of CSR-related projects. Insights gained from four focus groups amongst the Ok Tedi River indigenous communities show that while some members of the community are satisfied with the company’s efforts at the macro level, many have reservations about the effectiveness of the programs at the micro level on the village and family unit. The implementation of CSR activities are slow and in many instances do not effectively address stakeholder concerns.